2013
DOI: 10.1111/cup.12131
|View full text |Cite
|
Sign up to set email alerts
|

Maffucci syndrome with the spindle cell hemangiomas in the mucosa of the lower lip: a rare case report and literature review

Abstract: The presence of non-cutaneous vascular lesions in the syndrome of multiple enchondromas and subcutaneous hemangiomas, also named Maffucci syndrome, is exceedingly rare. Until now, non-cutaneous vascular lesions have been described in nine patients, while only three cases were present in the oral cavity; they were found in the tongue in two patients and in the lower lip in one patient. Herein, we report the second case of vascular lesions localized in the mucosa of lower lip in a patient with Maffucci syndrome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Fletcher proposed that SCH is caused by abnormalities of blood flow because of an arteriovenous shunt at the affected area . Injury is considered as a possible initiating factor because lesions occur frequently on the distal extremities . Furthermore, there are reports of SCH occurring on the precise site of repeated injections or surgical excisions .…”
Section: Discussionmentioning
confidence: 99%
“…Fletcher proposed that SCH is caused by abnormalities of blood flow because of an arteriovenous shunt at the affected area . Injury is considered as a possible initiating factor because lesions occur frequently on the distal extremities . Furthermore, there are reports of SCH occurring on the precise site of repeated injections or surgical excisions .…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemically, the cells lining the cavernous space and vacuolated epithelioid cells are positive for vimentin, CD31, CD34, and factor-VIII-related antigen, supporting the endothelial nature [ 1 3 , 5 , 7 9 , 11 , 12 , 15 ]. Weiss and Enzinger [ 13 ], Tosios et al [ 1 ], Ide et al [ 5 ], and Cai et al [ 9 ] reported that the lining cells and vacuolated epithelioid cells are positive for vimentin, CD31, CD34, and factor VIII, and in contrast, spindle cells are negative for endothelial markers. However, Sheehan et al [ 7 ] and Chavva et al [ 8 ] reported that spindle cells are positive for these markers.…”
Section: Discussionmentioning
confidence: 97%
“…In the majority of cases, the symptoms were not remarkable [ 18 ]. Most SCH lesions were fewer than 2 cm in size [ 3 , 5 , 7 , 9 , 11 ]. Only four cases in the head and neck region were more than 30 mm, including the present case, which was the only case of the oral lesion more than 30 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical presentation of Maffucci syndrome includes multiple enchondromas and vascular lesions, which are commonly associated with phleboliths (Biber et al, 2004;Cai et al, 2013). It can be diagnosed relatively easily solely on clinical grounds (Gao et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%